2021
DOI: 10.3390/s21030908
|View full text |Cite
|
Sign up to set email alerts
|

Feeling of Safety and Comfort towards a Socially Assistive Unmanned Aerial Vehicle That Monitors People in a Virtual Home

Abstract: Unmanned aerial vehicles (UAVs) represent a new model of social robots for home care of dependent persons. In this regard, this article introduces a study on people’s feeling of safety and comfort while watching the monitoring trajectory of a quadrotor dedicated to determining their condition. Three main parameters are evaluated: the relative monitoring altitude, the monitoring velocity and the shape of the monitoring path around the person (ellipsoidal or circular). For this purpose, a new trajectory generato… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In this sense, the results showed that the trajectory planner correctly determines the references for the UAV's position and yaw angle according to the position and orientation of the person, while the 3D virtual quadrotor reproduces the flight based on the UAV state information received from the UAV Simulator. More details about the trajectory planner operation can be found in our previous works [13,24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, the results showed that the trajectory planner correctly determines the references for the UAV's position and yaw angle according to the position and orientation of the person, while the 3D virtual quadrotor reproduces the flight based on the UAV state information received from the UAV Simulator. More details about the trajectory planner operation can be found in our previous works [13,24].…”
Section: Discussionmentioning
confidence: 99%
“…In the current implementation of the planner, it is possible to configure the tracking trajectory to define the height at which the UAV flies, as well as the trajectory (circular or elliptical) it describes around the person, to suit the user's preferences. Details of this planner can be found in [24].…”
Section: Uav Simulatormentioning
confidence: 99%
“…The link between the headset and the robotic platform was created using the Message Queueing Telemetry Transport (MQTT) communication protocol [ 25 ]. MQTT is a lightweight protocol for IoT messaging and is widely used in robot control systems [ 26 , 27 , 28 , 29 , 30 , 31 ]. It was our choice because it has a small computational overhead and was easy to integrate into our system.…”
Section: Methodsmentioning
confidence: 99%
“…The implementation of a completely functional VE facilitates learning among people of various ages, and is safer than real-world experience [ 14 ]. VR is also cost-efficient and capable of reducing potential risks [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%